Reversibility of the Other-Race Effect in Face Recognition During Childhood - Sangrigoli, S.; Pallier, C.; Argenti, A.-M.; Ventureyra, V.A.G.; de Schonen, S. (Psychological Science, 2005)
Early experience with faces of a given racial type facilitates visual recognition for this type of face relative to others. To assess whether this so-called other-race effect can be reversed by subsequent experience with new types of faces, we tested adults of Korean origin who were adopted by European Caucasian families when they were between the ages of 3 to 9. The adoptees performed a face recognition task with photographs of Caucasian and Asian faces. They performed exactly like a control group of French participants, identifying the Caucasian faces better than the Asiatic ones. In contrast, a control group of Koreans showed the reverse pattern. This result indicates that the face recognition system remains plastic enough during childhood to reverse the other-race effect.